Anodontophora tuvensis gen. nov. et sp. nov. (Collembola: Onychiuridae: Tetrodontophorinae) - Pomorski, Romuald J. (Zootaxa, 2007)
Anodontophora tuvensis––a new genus and species of onychiurids with a fully developed and functional furca is described. It is easily distinguishable by the lack of postantennal organ. Based on the structure of maxillae the new genus is related to the genera Tetrodontophora Reuter, 1882 and Homaloproctus Börner, 1909.